2019
DOI: 10.31025/2611-4135/2019.13857
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Recycled Polypropylene, Cellulose and Newsprint Fibres for Production of Green Composites

Abstract: This work investigates the feasibility of using the recycled polypropylene (rPP), cellulose (CF) and newsprint (NP) fibres in polyolefin reinforced composites. Recycled PP filled with 40 wt.% of cellulose (rPP/CF) or newsprint (rPP/NP), with the addition of impact modifier (IM) and compatibilizing agent (CA), have been prepared with extrusion melting and injection moulding. Melting and crystallization behaviour of plain matrix and composites were measured by differential scanning calorimetry (DSC). Morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, WP-ON presented the highest mechanical properties for flexural strength (25%) [ 71 ]. Recycled PP filled with WP as newspaper (WP-N) was compared with better quality and more expensive filler: cellulose with a special bleaching pretreatment [ 69 ]. The results showed an improvement in tensile strength (26% and 56%) and stiffness (47% and 16%) for WP-N and cellulose, respectively, compared to recycled PP.…”
Section: Waste Paper-polymeric Compositesmentioning
confidence: 99%
“…However, WP-ON presented the highest mechanical properties for flexural strength (25%) [ 71 ]. Recycled PP filled with WP as newspaper (WP-N) was compared with better quality and more expensive filler: cellulose with a special bleaching pretreatment [ 69 ]. The results showed an improvement in tensile strength (26% and 56%) and stiffness (47% and 16%) for WP-N and cellulose, respectively, compared to recycled PP.…”
Section: Waste Paper-polymeric Compositesmentioning
confidence: 99%
“…One factor which affects mechanical properties is crystallinity. In the literature, two opposite trends may be found: the crystallinity degree (Xc) increases due to the fibers acting as nucleating agents [ 23 ] or the crystallinity degree does not change much with increasing fiber content [ 24 ]. In the case of the investigated composites, it was found that the fibers induced crystal nucleation of the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…For environmental tests, secondary raw materials obtained from the recycling of beverage bottles-rPE and rPP-newsprint (NP) and the composites produced from them were used; see Table 1. The paper [25] presents a method for producing the secondary raw materials and their properties. The thermoforming process developed under the Ceplafib project [22] was used to obtain polypropylene matrix composites reinforced with cellulose fibres (rPP/NP) and polyethylene-based composites reinforced with cellulose fibres (rPE (HD:LD 50:50) + NP, rPE (HD:LD 70:30) + NP).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the rPE/NP and rPP/NP composites, including mechanical, thermal and morphological properties were published by Fajs P. et al [24] and Bogataj V.Z. et al [25].…”
Section: Introductionmentioning
confidence: 99%